Peran Sikap Makanan Lokal Dalam Memediasi Pengaruh Nilai Pengalaman Dan Media Sosial Terhadap Keinginan Membeli Pada Wisatawan Domestik Generasi Milenial Di Kota Palembang - Anita, Anita (Politeknik Pariwisata Medan, 2024)
This study aims to investigate the role of attitudes towards local food in mediating the influence of experiential value and social media on purchasing intention among domestic millennial tourists in Palembang City. The method utilized is structural equation modeling with Partial Least Squares (SEM-PLS). The population targeted in this study consists of domestic millennial tourists visiting Palembang City. A sample of 130 respondents was chosen using Hair's technique. Data collection was carried out through questionnaires and literature review. Data analysis was conducted using the SEM-PLS4 application with path analysis, which examines the influence on intervening variables. The results indicate that experiential value towards purchasing intention, experiential value towards attitudes towards local food, the role of attitudes towards local food towards purchasing intention, and experiential value towards purchasing intention through the role of attitudes towards local food have a positive and significant impact. Meanwhile, social media towards purchasing intention, social media towards attitudes towards local food, and social media towards purchasing intention through the role of attitudes towards local food do not have a significant impact.